2012
DOI: 10.1523/jneurosci.6459-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Mechanisms of Individual Differences in Human Effort-Based Decision-Making

Abstract: Preferences for different combinations of costs and benefits are a key source of variability in economic decision-making. However, the neurochemical basis of individual differences in these preferences is poorly understood. Studies in both animals and humans have demonstrated that direct manipulation of the neurotransmitter dopamine (DA) significantly impacts cost/benefit decision-making, but less is known about how naturally occurring variation in DA systems may relate to individual differences in economic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
261
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(279 citation statements)
references
References 62 publications
15
261
2
1
Order By: Relevance
“…Simulation experiments suggest that a striatal signal begins to emerge after 2 h (Ceccarini et al, 2012); empirical data indicate that tracer equilibrium is clearly achieved by 3 h (Vernaleken et al, 2011). The present study plus work conducted elsewhere further confirm that scans of 180-210 min are sufficient to measure striatal DA release (Buckholtz et al, 2010a;Buckholtz et al, 2010b;Treadway et al, 2012). Fourth, the associations between cue-induced DA release and self-reported drug craving are correlations and do not indicate causality.…”
Section: Discussionsupporting
confidence: 69%
“…Simulation experiments suggest that a striatal signal begins to emerge after 2 h (Ceccarini et al, 2012); empirical data indicate that tracer equilibrium is clearly achieved by 3 h (Vernaleken et al, 2011). The present study plus work conducted elsewhere further confirm that scans of 180-210 min are sufficient to measure striatal DA release (Buckholtz et al, 2010a;Buckholtz et al, 2010b;Treadway et al, 2012). Fourth, the associations between cue-induced DA release and self-reported drug craving are correlations and do not indicate causality.…”
Section: Discussionsupporting
confidence: 69%
“…Dopamine function, which has long been implicated in willingness to expend effort (Salamone, 2009;Salamone et al, 2007;Treadway et al, 2012b), may also act on these regions to affect effortful decision making (Schweimer and Hauber, 2006;Schweimer et al, 2005), and thus its contribution to cognitive effort is currently under study. The overlapping-yet-distinct effects observed in the present experiments suggest that regions not required for physical effort-based decision making, such as the prefrontal cortex, may in fact be necessary for decision making with cognitive effort costs (Schmidt et al, 2012), and the NAc' prevalence in the effort literature warrants future consideration of its involvement in choice on the rCET.…”
Section: Discussionmentioning
confidence: 99%
“…Regions deemed inessential in physical effort (eg, the prefrontal cortex; Walton et al, 2003b) have been shown to have a prominent role in human cognitive effort Schmidt et al, 2012). Furthermore, these human studies have emphasized how individual differences in brain function influence individual differences in effort expenditure (Treadway et al, 2012b), an examination all but absent from animal effort literature (but see Randall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…their motivation for a reward as measured by a willingness to work for it (e.g. [94,95]). Consistently, non-invasive neuroimaging has shown differential effects in the striatum during reward anticipation in healthy controls and a reduction thereof across different stages of schizophrenia (e.g.…”
Section: (D) the Case Of Schizophreniamentioning
confidence: 99%